Child Separation and the Stolen Generation of Brazil: Indigenous Peoples’ (Un)Freedom in Amazonia - Ana Luiza Morais Soares (Latin American Research Review)
This article examines questions pertaining to Indigenous people’s citizenship status, the problematic definition of orphanhood, rule of law, and structural racism in Brazilian society. The definition of orphanhood was articulated in a way that allowed for the extralegal abuse and racialized exploitation of labor to continue long past the legal end of Indigenous slavery (1755). Indigenous persons’ legal status, the definition of orphanhood, and guardianship laws worked together to legitimate the permanence of child separation as a means for wealthier Brazilians to get free child labor. The article uncovers the ambiguities in defining Indigenous people’s legal status, making citizenship status a subjective determination contested on a case-by-case basis. With this foreground understanding, the article presents the practice of child separation and the created discourse to legitimize Indigenous, Black, and mixed-race children as unpaid criadas de casa (housemaids).